Dynamics of Public Trust in Government amid Information Disruption in Southeast Asia - Yunaz Farada Yoga; R. Abdul Haris (Jurnal Ragam Pengabdian, 2026)
Information disruption characterized by the acceleration of digital communication flows, the spread of misinformation and disinformation, and the fragmentation of online public spaces have affected the pattern of public trust in governments in Southeast Asia. This study aims to analyze the dynamics of public trust in the context of information disorder, paying attention to the role of institutional factors and the cognitive capacity of the community. The study used a mixed-methods approach by combining a quantitative survey of 720 adult respondents (≥18 years) recruited through stratified purposive sampling in three Southeast Asian countries, Indonesia, Malaysia, and the Philippines, as well as in-depth interviews with 24 key informants consisting of government officials, journalists, academics, and civil society representatives. Regression analysis and differential testing showed that exposure to disinformation content was significantly negatively associated with the level of public trust in government institutions, particularly in the credibility aspect of policy communication. However, the results of the study also show that digital media literacy and perception of government transparency function as protective variables that can moderate the negative impact of information disruption. The qualitative findings confirm that the decline in public trust is not only triggered by the existence of false information, but also by weaknesses in government communication responses that are considered less responsive and participatory. This research makes a theoretical contribution to the understanding of public trust in the digital information ecosystem in Southeast Asia and offers policy implications in the form of strengthening public communication strategies, improving information literacy, and developing cross-sectoral collaborative mechanisms in the face of information disruption.